2019
DOI: 10.1124/jpet.119.257592
|View full text |Cite
|
Sign up to set email alerts
|

Doxorubicin Activates Ryanodine Receptors in Rat Lymphatic Muscle Cells to Attenuate Rhythmic Contractions and Lymph Flow

Abstract: Doxorubicin is a risk factor for secondary lymphedema in cancer patients exposed to surgery or radiation. The risk is presumed to relate to its cytotoxicity. However, the present study provides initial evidence that doxorubicin directly inhibits lymph flow and this action appears distinct from its cytotoxic activity. We used real-time edge detection to track diameter changes in isolated rat mesenteric lymph vessels. Doxorubicin (0.5-20 mmol/l) progressively constricted lymph vessels and inhibited rhythmic cont… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
29
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 24 publications
(35 citation statements)
references
References 60 publications
3
29
1
Order By: Relevance
“…Such lymphatic dysfunction can occur prior to treatments of surgical dissection and/or RT, suggesting that cancer progression, particularly LN metastasis, contributes to lymphatic dysfunction in cancer patients prior to surgery and RT. While there is evidence that chemotherapy may potentially contribute to the development of cancer-acquired LE [66][67][68][69], further longitudinal studies are needed to understand all the contributing factors that can cause lymphatic dysfunction. Nonetheless, recent results in Figure 7 confirm the results of other studies showing subclinical edema measured with bioimpedance of water content in the arms in breast cancer patients prior to first-line treatment [70,71].…”
Section: The Effects Of Metastasis and Cancer Progression On Lymphatimentioning
confidence: 99%
“…Such lymphatic dysfunction can occur prior to treatments of surgical dissection and/or RT, suggesting that cancer progression, particularly LN metastasis, contributes to lymphatic dysfunction in cancer patients prior to surgery and RT. While there is evidence that chemotherapy may potentially contribute to the development of cancer-acquired LE [66][67][68][69], further longitudinal studies are needed to understand all the contributing factors that can cause lymphatic dysfunction. Nonetheless, recent results in Figure 7 confirm the results of other studies showing subclinical edema measured with bioimpedance of water content in the arms in breast cancer patients prior to first-line treatment [70,71].…”
Section: The Effects Of Metastasis and Cancer Progression On Lymphatimentioning
confidence: 99%
“…DOX appears to impair lymph flow by tonically activating ryanodine receptors (RYRs) to mediate Ca 2+ release from the sarcoplasmic reticulum of LMCs, thereby causing "calcium leak" and establishing persistently elevated levels of cytosolic free calcium ([Ca 2+ i ]). Because rhythmic contractions of LMCs rely on the cyclic elevation of [Ca 2+ i ] to mediate contraction, followed by restoration of resting levels of [Ca 2+ i ] to permit relaxation, the tonic "calcium leak" induced by DOX disrupts rhythmic contractions and impairs lymph flow (Stolarz et al, 2019). Importantly, we noted that rhythmic contractions in isolated LVs can be restored by blocking RYRs using high concentrations of ryanodine or therapeutic concentrations of dantrolene (DANT).…”
Section: Introductionmentioning
confidence: 97%
“…In this respect, we recently reported that DOX acutely disrupts the rhythmic contractions of isolated rat mesenteric LVs and attenuates lymph flow in vivo at clinically achievable plasma concentrations (Stolarz et al, 2019). DOX appears to impair lymph flow by tonically activating ryanodine receptors (RYRs) to mediate Ca 2+ release from the sarcoplasmic reticulum of LMCs, thereby causing "calcium leak" and establishing persistently elevated levels of cytosolic free calcium ([Ca 2+ i ]).…”
Section: Introductionmentioning
confidence: 99%
“…A single LV was visualized, and increasing concentrations of cromakalim or minoxidil sulfate (0.01–10 μmol/l; log units) were added to the superfusate bathing the mesentery for 15 minutes at each drug concentration. Customized software developed in collaboration with our institution’s Nanomedicine Center was used to track individual lymph cells in flow as described earlier in detail ( Sarimollaoglu et al, 2018 ; Stolarz et al, 2019 ). Using these data files, flow velocity and positive volumetric flow were calculated to evaluate the effect of KCOs on lymph flow in vivo.…”
Section: Methodsmentioning
confidence: 99%
“…Origin 9.1 software (OriginLab Corporation, Northampton, MA, USA) was used to analyze the following contractile parameters: end diastolic diameter (EDD), end systolic diameter (ESD), frequency of contraction, and amplitude of contraction. Flow per unit length in a single lymph vessel was calculated using the equation: π/4(EDD 2 -ESD 2 )F, as previously described (Stolarz et al, 2019).…”
Section: Mesenteric Lvsmentioning
confidence: 99%